Analysis of the Effectiveness of the T² Hotelling Control Chart in Concrete Control - Syilviani; Rina Filia Sari (Information Technology and Science (ITScience), 2025)
In the world of construction, concrete quality plays a very important role because it directly affects the strength and durability of building structures. The purpose of this research is to appraise and evaluate the efficiency of using the T² Hotelling control chart method in controlling concrete quality at PT. Wijaya Karya Beton Tbk by analyzing three main concrete quality parameters: slump, compressive strength, and tensile strength, based on data collected from January to February 2025. The methods employed include multivariate analysis approaches, such as correlation tests, multivariate normality tests, Johnson transformation to improve non-normally distributed data, and the application of generalized variance control charts and T² Hotelling control charts. The results of the study indicate a significant correlation between concrete quality variables; however, the initial data did not meet the assumption of multivariate normality, necessitating the Johnson transformation, which proved effective in improving data distribution and enabling the application of Hotelling's T² analysis. Based on the control charts, most observations remained inside the established control limits; however, some samples fell outside the boundaries, indicating process disturbances. Overall, this study concluded that the Hotelling T² method is effective in detecting process nonconformities at an early stage, thereby serving as a foundation for continuous improvement in concrete production quality and making a significant contribution to strengthening the quality control system in the national construction sector.